Pengembangan Sistem Informasi Rawat Inap dengan Metode Rational Unified Process (Studi Kasus Rumah Sakit Khusus Hayunanto Medical Center Malang) - Candra Dwi Kusuma; Yusi Tyroni Mursityo; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Hayunanto Medical Center Special Hospital is a special hospital that focuses on mental health rehabilitation and drug dependency rehabilitation services in Malang. One of the health services that requires a fast flow of information at this hospital, especially in the inpatient department. However, the implementation of data collection continues to occur in documents or forms which are then stored only with a sheet of paper in the folder making data sorting too long, so the effect on the data discovery process takes so long, because patient data is not stored in storage memory. In the application of a manual system, it will be difficult to control because the processing is carried out by humans, so the occurrence of errors will be even greater, such as the occurrence of repeated recording or data redundancy. This system was created using the Rational Unified Process (RUP) method which includes the stages of inception, elaboration, construction, and transition. Inpatient information system has been made with the results of validation tests to test functional systems produce 100% valid and compatibility tests to test non-functional requirements obtained by 2 critical problems in 2 applications. User Acceptance Testing conducted with 5 correspondents from each user shows the inpatient service information system can still be well received by the user.